Systematic review of interventions targeting sickness absence among pregnant women in healthcare settings and workplaces. Issue 10 (25th October 2018) - Pedersen, Pernille; Labriola, Merete; Nielsen, Claus Vinther; Maimburg, Rikke Damkjær; Nohr, Ellen Aagaard; Momsen, Anne-Mette
Abstract : Objectives: The high rate of sickness absence from work during pregnancy is recognised as a problem, and may be higher than necessary from a health perspective. The aim was to evaluate the effectiveness of interventions in healthcare settings and workplaces targeting sickness absence among pregnant women. Methods: Studies were eligible if they included pregnant women participating in any intervention in healthcare settings or workplaces. The outcome was length of sickness absence in days or number of episodes. Study design had to be either randomised controlled trials (RCTs) or quasi-experimental studies. The search for studies was conducted in PubMed, Scopus, CINAHL, PsycINFO, ClinicalTrials.gov and WHO trial registry. Risk of bias was assessed by the Joanna Briggs Institute standardised quality assessment instrument. Results: A total of nine studies were quality assessed and of these, four were excluded due to insufficient methodological quality. Five RCTs conducted in healthcare settings in Sweden and Norway were included. Due to heterogeneity, meta-analysis was not performed. Two RCTs examined complementary and alternative medicine and three RCTs the effect of physical exercise. In general, the frequency of women on sickness absence was lower in the intervention groups than the control groups, however, only among pregnant women who participated in a 12-week exercise programme, the frequency was significantly lower (22% vs 30%, p=0.04). Conclusion: The evidence of interventions targeting sickness absence among pregnant women in healthcare settings is sparse, and no studies were conducted at workplaces. Future interventions including physical activity provided in collaboration with healthcare settings and workplaces are requested. Studies should measure sickness absence based on valid methods, measure compliance to the intervention and provide transparency of statistical methods. PROSPERO registration number: CRD42018084802.